The Effect of Reading Comprehension Skills on The Ability of Solving Word Problems to Fourth Grade Students of Public Elementary Schools in Alian Subdistrict in Academic Year of 2019/2020 - Noviana, Rizki; Joharman, Joharman; Chamdani, Muhamad (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The study aimed to prove the effect of reading comprehension skills on the ability of solving word problems and to determine the effect of reading comprehension skills on the ability of solving word problems to fourth grade students of public elementary schools in Alian Sub-district in academic year of 2019/2020. It was quantitative research with correlation method. The sampling method was cluster random sampling with the help of Statistical Product and Service Solution (SPSS) application version 16. From data analysis, correlation coefficient of reading comprehension skills on the ability of solving word problems was 0,610 and it was strong correlation. Reading comprehension skills affected the ability of solving word problems by 37.2%. It concludes that there is positive effect of reading comprehension skills on the ability of solving word problems. It means that the higher students' reading comprehension skills, the higher studentsâ€™ word problems solving ability and vice versa.Â  Reading comprehension skills contributed 37.2% on the ability of solving word problems.